Keterlibatan Ibu Dalam Mengembangkan Kemampuan Literasi Anak Berkebutuhan Khusus - Putra, Wisnu Wijaya; , Dr. Lisnawati Ruhaena,M.Si, Psi (2018)
Stimulation of literacy skills is done since pre-school and this is certainly reaping the debate Children development age should be considered especially for those who have special needs of course require special treatment. It is expected that the mother as an individual who is close to the children has special strategies to overcome the uniqueness that the children have, so the mother must also understand the characteristics of the children. This research uses qualitative method with the number of informants of five mother's whith children who are undergoing therapy at we care gemolong institution. This research uses interview method, observation and documentation as the data collection tool. The data analysis used is content analysis. The result of this research shows that the role of mother is fully involved in assisting children to socialize and to fulfill children's need. In addition, the mother's contribution in developing literacy ability is to give support in material's need, such as giving supporting facilities. They are providing schedule in adding more books, learning videos, internet facilities, and games which is to stimulate children's literacy ability. Those are evident that they can enhance children's literacy ability. Unfortunately, this research has found that some mothers do not give supporting facilities yet, so that the development of children's literacy ability is low. Furthermore, the role of mother is also to give support in morality when children's motivation is low, such as singing fun songs, giving prizes, asking quizzes and showing pictures. Moreover, a mother also should provide quality time in a day around thirty minutes until two hours to enhance children's literacy ability. Keywords: children with special needs, literacy development, parental support.